Microbial and Geochemical Evidence of Permafrost Formation at Mamontova Gora and Syrdakh, Central Yakutia - Cherbunina, M. Yu.; Karaevskaya, E. S.; Vasil’chuk, Yu. K.; Tananaev, N. I.; Shmelev, D. G.; Budantseva, N. A.; Merkel, A. Y.; Rakitin, A. L.; Mardanov, A. V.; Brouchkov, A. V.; Bulat, S. A. (Frontiers in Earth Science, 2021)
Biotracers marking the geologic history and permafrost evolution in Central Yakutia, including Yedoma Ice Complex (IC) deposits, were identified in a multiproxy analysis of water chemistry, isotopic signatures, and microbial datasets. The key study sections were the Mamontova Gora and Syrdakh exposures, well covered in the literature. In the Mamontova Gora section, two distinct IC strata with massive ice wedges were described and sampled, the upper and lower IC strata, while previously published studies focused only on the lower IC horizon. Our results suggest that these two IC horizons differ in water origin of wedge ice and in their cryogenic evolution, evidenced by the - differences in their chemistry, water isotopic signatures and the microbial community compositions. Microbial community similarity between ground ice and host deposits is shown to be a proxy for syngenetic deposition and freezing. High community similarity indicates syngenetic formation of ice wedges and host deposits of the lower IC horizon at the Mamontova Gora exposure. The upper IC horizon in this exposure has much lower similarity metrics between ice wedge and host sediments, and we suggest epigenetic ice wedge development in this stratum. We found a certain correspondence between the water origin and the degree of evaporative transformation in ice wedges and the microbial community composition, notably, the presence of Chloroflexia bacteria, represented by Gitt-GS-136 and KD4-96 classes. These bacteria are absent at the ice wedges of lower IC stratum at Mamontova Gora originating from snowmelt, but are abundant in the Syrdakh ice wedges, where the meltwater underwent evaporative isotopical fractionation. Minor evaporative transformation of water in the upper IC horizon of Mamontova Gora, whose ice wedges formed by meltwater that was additionally fractionated corresponds with moderate abundance of these classes in its bacterial community.